Optimalisasi Kegiatan Magang Mandiri dalam Peningkatan Kompetensi Mahasiswa dan Pemahaman Dunia Industri Properti : Studi Kasus di PT Taman Timur Regensi - Ruri Istia Damayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Independent internship activities are one of the educational strategies that aim to bridge theory with the practice of the world of work. This study aims to describe the implementation of independent internships for students at PT Taman Timur Regensi Surabaya and its contribution to improving students' competence and understanding of the property industry. The research method uses a qualitative descriptive approach with data collection techniques in the form of direct observation, interviews, and documentation studies. The results of the study indicate that internship activities support the improvement of students' technical skills, especially in the fields of project administration, management of legal documents, and understanding of housing development flows. In addition, students' soft skills, such as professional communication, teamwork, and time management, have also experienced significant development. In conclusion, independent internships at PT Taman Timur Regensi are an effective medium to prepare students to face the world of work in the property industry in a more prepared and competent manner.